2006
DOI: 10.1007/s00280-006-0321-7
|View full text |Cite
|
Sign up to set email alerts
|

Antitumour action of 5,6-dimethylxanthenone-4-acetic acid in rats bearing chemically induced primary mammary tumours

Abstract: This study shows for the first time that DMXAA has significant in vivo antitumour activity against non-transplanted autochthonous tumours and in a host species other than the mouse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…Interestingly, however, we found that the vascular disrupting effects of DMXAA on subcutaneous tumors did not extend to either the 344SQ-ELuc metastases obtained following intracardiac injection of these cells, or to the spontaneously arising tumors in the K-ras LA1/+ GEMM model of NSCLC. Indeed, the majority of successful pre-clinical studies evaluating the utility of DMXAA were carried out in subcutaneous tumor models, with relatively few studies examining the effects of DMXAA on tumors in other anatomical sites [37], [38]. Echoing our results, experiments employing a different vascular disrupting drug, flavone acetic acid (FAA), vessel disruption was seen in subcutaneous tumors, but not systemic tumors [39].…”
Section: Discussionsupporting
confidence: 55%
“…Interestingly, however, we found that the vascular disrupting effects of DMXAA on subcutaneous tumors did not extend to either the 344SQ-ELuc metastases obtained following intracardiac injection of these cells, or to the spontaneously arising tumors in the K-ras LA1/+ GEMM model of NSCLC. Indeed, the majority of successful pre-clinical studies evaluating the utility of DMXAA were carried out in subcutaneous tumor models, with relatively few studies examining the effects of DMXAA on tumors in other anatomical sites [37], [38]. Echoing our results, experiments employing a different vascular disrupting drug, flavone acetic acid (FAA), vessel disruption was seen in subcutaneous tumors, but not systemic tumors [39].…”
Section: Discussionsupporting
confidence: 55%
“…However this agent failed in a Phase I clinical trial and showed no activity in rat tumor models (42), raising the question of possible species-specificity. In an attempt to obtain similar drugs that produced tumor hemorrhagic necrosis, the molecular structure of FAA was modified, generating several compounds; 5,6-dimethyllxanthenone-4-acetic acid (DMXAA) was the compound with the highest potency and it also showed activity against a rat mammary carcinoma (43). Similar to FAA, DMXAA showed anti-tumor activity in different mouse models (44).…”
Section: Clinical-translational Advancesmentioning
confidence: 99%
“…For examples, they can be categorized by locations such as subcutaneous [51,59] , intramuscular [60][61][62] or visceral organ [57] tumors; by destination relative to source graft such as orthotopic [63][64][65] or ectopic tumors; by carcinogenesis such as primary [26,48,65,66] or secondary tumors; by graft origins such as allograft [63] or xenograft human [61,67,68] or animal [69] tumors; and by immune status of tumor recipient such as the tumors growing in immunocompetent or immunodeficient [64,68] animals. A wide range of diverse VDA effects have been observed in various tumor models [70,71] .…”
Section: Animal Tumor Modelsmentioning
confidence: 99%